2012
DOI: 10.6116/kjh.2012.27.3.67
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ssanghwa-tang Extract on Antioxidant and Anti-aging Enzyme Activities

Abstract: Objectives : The present study was designed to investigate effects of Ssanghwa-tang (Shuānghuā-gēng) on oxidation/reduction reaction-related and aging-related enzymes in vitro.Methods : We performed MTT assay, collagenase inhibition assay, elastase inhibition assay, tyrosinase inhibition assay, DPPH free radical scavenging assay, SOD-like activity and xanthine oxidase (XO) inhibition assay. Results : The 50% ethanol (EtOH) extract of Ssanghwa-tang (SHT) showed 55% inhibition of collagenase activity, and 42% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Collagen, a major component of the extracellular matrix, is a matrix protein produced by fibroblasts in the skin. The regulation of biosynthesis and degradation of collagen is a core metabolism process of skin aging and skin wrinkle formation (Park et al, 2012). The results of the collagenase enzyme inhibition assay using Areca nut extracts showed better inhibition of collagenase activity than EGCG in all extracts.…”
Section: Collagenase Enzyme Inhibition Assaymentioning
confidence: 92%
“…Collagen, a major component of the extracellular matrix, is a matrix protein produced by fibroblasts in the skin. The regulation of biosynthesis and degradation of collagen is a core metabolism process of skin aging and skin wrinkle formation (Park et al, 2012). The results of the collagenase enzyme inhibition assay using Areca nut extracts showed better inhibition of collagenase activity than EGCG in all extracts.…”
Section: Collagenase Enzyme Inhibition Assaymentioning
confidence: 92%
“…In recent studies, SHT has been reported to possess many functions, such as protection against acute hepatotoxicity, anti-melanogenic activity, and inhibitory effects on bone loss [9][10][11] . It has also been reported to exert analgesic, anti-convulsant, anti-oxidative, anti-aging and anti-inflammatory effects [12][13][14] . A recent study showed that SHT exerted anti -inflammatory effects on cigarette smoke-induced airway inflammation by modulation pro-inflammatory cytokines through the matrix metallopeptidase 9…”
Section: Introductionmentioning
confidence: 99%